Digital Beamforming Techniques for Spaceborne Radar Remote Sensing - Krieger, Gerhard; Gebert, Nicolas; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2006)
This paper introduces the innovative concept of multidimensional waveform encoding for spaceborne synthetic aperture radar. The combination of this technique with digital beamforming on receive enables a new generation of SAR systems with improved performance and flexible imaging capabilities. Implementation specific issues will be discussed and performance examples demonstrate the potential for different remote sensing applications.
DLR Import::2019-04-03